Efficient photoactivation of a Diels-Alderase ribozyme - Nierth, Alexander; Singer, Marco; Jäschke, Andres (Chemical communications, 2010)
Here we report the first example of a photoactivatable ribozyme which catalyzes a bimolecular reaction of two small organic molecules with multiple turnover, under control of a photo-cleavable protecting group by exploiting the structural significance of a single hydrogen bond.